2017
DOI: 10.3390/ijerph14020180
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Heat Exposure and Sleep Restriction on Firefighters’ Work Performance and Physiology during Simulated Wildfire Suppression

Abstract: This study was designed to examine the effects of ambient heat on firefighters’ physical task performance, and physiological and perceptual responses when sleep restricted during simulated wildfire conditions. Thirty firefighters were randomly allocated to the sleep restricted (n = 17, SR; 19 °C, 4-h sleep opportunity) or hot and sleep restricted (n = 13, HOT + SR; 33 °C, 4-h sleep opportunity) condition. Firefighters performed two days of simulated, intermittent, self-paced work circuits comprising six firefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…Therefore, we may have expected that those in the sleep restricted conditions were more likely to consume the most kilojoules during this snacking period. Previously published results from this study have shown no difference in sleep quality between conditions, and confirmed that total sleep time was less in the sleep restricted condition [49]. Perhaps with a greater number of consecutive days of sleep restriction, or sleep deprivation (e.g.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Therefore, we may have expected that those in the sleep restricted conditions were more likely to consume the most kilojoules during this snacking period. Previously published results from this study have shown no difference in sleep quality between conditions, and confirmed that total sleep time was less in the sleep restricted condition [49]. Perhaps with a greater number of consecutive days of sleep restriction, or sleep deprivation (e.g.…”
Section: Discussionsupporting
confidence: 87%
“…Statistical significance was defined as p < 0.05 and post hoc pairwise comparisons were performed using a Bonferroni correction. The data analysed in the current study were secondary to the primary aims of the study, with primary outcomes published elsewhere [8,[12][13][14][15][48][49][50][51][52][53][54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations